Optimasi Pemasaran Digital sebagai Program Pendamping pada Catering dan Gado-Gado Bu Tatik dalam Meningkatkan Omset - Febriandini, Elvina; Rohaini , Elvina; Rahayu , Emma Puji; Anggraeni , Erlia Irma; Aryati, Ervira Budi; Afandi, Akhmad Jazuli (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The use of digital marketing is really needed by business people, including small businesses. This internship activity (Sharia business practice) is carried out to provide education to small business actors, especially those in the catering and Gado-Gado Bu Tatik (shop catering) businesses, about the importance of using social media as a promotional tool. The method used in this activity is the preparation, implementation, results, and evaluation stages. Through this activity, it is hoped that Bu Tatik's Catering & Gado-Gado (Shop Catering) business will have a proper understanding of the importance of utilizing digital marketing so that it can carry out efficient digital marketing and have a good impact on increasing income. The results of this activity show that the use of digital marketing using social media is very helpful in marketing efforts for Bu Tatik's Catering & Gado-Gado (Shop Catering) business. Through the use of digital marketing using social media, you can expand the market and increase awareness of the sales products of Bu Tatik's Catering & Gado-Gado business (Shop Catering) so that you can increase turnover and profits.